Milestones of daycare surgery activities at Karnali Teaching Hospital over a period of two years - Thapaliya, Narad Prasad; Menyengbo, Suryaman; Giri, Rajendra Mani; Rokaya, Poojan; Kathayat, Tufan; Bista, Binamra (Journal of General Practice and Emergency Medicine of Nepal, 2024)
Introduction: Minor surgery has been performed regularly in Hospitals, surgical, outpatient, and emergency departments as a day care surgery for years. In modern-day hospitals, there are established principles for ambulating surgical patients as early as possible. This idea led to the concept of daycare surgery. Method: A retrospective study was conducted at the Karnali Teaching Hospital, Jumla, Nepal, over two years from 17 July 2021 to 16 July 2023 under the Department of Surgery, and the data were analyzed. A total of 580 patients who underwent daycare surgeries in the department of surgery were included in the study. Result: Total of 580 minor surgeries (daycare surgery), were performed. Total males were 340 (56.5%), and females were 240(43.5%). Among them, 348 (60%) were done under local anesthesia and 232 (40%) under intravenous anesthesia. Incision and drainage for abscess were done in 155 (26.5%) patients, Excision of the lump was done in 150 (25.5%), and non-scalpel vasectomy was done in 120 (20.5%) patients. Conclusion: During two years, daycare surgery was 57.5% of total surgery. By organising good daycare surgery services, the percentage of cases can be increased and a patient-friendly environment can be created.